TRADISI NELAYAN TERHADAP PANTANGAN MELAUT PADA MALAM DAN HARI JUMAT DITINJAU DARI HUKUM ADAT KAMPONG GOSONG TELAGA UTARA ACEH SINGKIL - Khairuddin Khairuddin; Husniati Atami (STIS Nahdlatul Ulama Aceh, 2021)
This study aims to analyze how the views of the people of Gosong Telaga Utara, North Singkil District on the taboo to go to sea at night and Friday and analyze how customary law reviews the taboo to go to sea at night and Friday in Kampong Gosong Telaga Utara, North Singkil District. The type of research is descriptive-qualitative research with a case study approach. The results showed that the majority of the people obeyed the prohibition on going to see at night and Friday because it was forbidden since their ancestors if violated it was feared that they would get a big disaster. Abstinence from going to sea at night and Friday in Kampong Gosong Telaga Utara has legal force, namely customary law for violating it, strict sanctions will be applied to it. The sanction is to pay Rp. 500,000 and is used for the purposes of mosques, canoes, or bots that violate are not given to the sea for 2-7 days. For fishermen outside the area who take North Telaga Gosong fish, 30% of their catch will be taken and pay Rp. 500,000.